Treating hoarding disorder with compassion‐focused therapy: A pilot study examining treatment feasibility, acceptability, and exploring treatment effects. (4th July 2019) - Chou, Chia‐Ying; Tsoh, Janice Y.; Shumway, Martha; Smith, Lauren C.; Chan, Joanne; Delucchi, Kevin; Tirch, Dennis; Gilbert, Paul; Mathews, Carol A.
Abstract : Objectives: Hoarding disorder (HD) was recognized as a psychiatric disorder in 2013. Existing literature suggests room for improvement in its treatment. The current pilot study aimed to provide an initial evaluation on the potential of compassion‐focused therapy (CFT) as an intervention for HD, with the primary aim being assessing its feasibility and acceptability, and the secondary being evaluating its effects. Design: Both CFT and a second round of the current standard of treatment and cognitive behavioural therapy (CBT) were investigated in the current study as follow‐up treatment options for individuals who had completed CBT but were still significantly symptomatic. Methods: Forty eligible individuals were enrolled (20 in each treatment). Treatment feasibility and acceptability were assessed by quantitative and qualitative measures. To explore treatment effects, HD symptom severity, HD‐related dysfunctions, and their underlying mechanisms were assessed pre‐treatment and post‐treatment. Results: Retention rates were 72% for CFT and 37% for CBT. All participants and 79% of the participants rated CFT and CBT, respectively, as good or excellent. After receiving CFT as a follow‐up treatment, HD symptom severity dropped below the cut‐off point for clinically significant HD for 77% of the treatment completers, and 62% achieved clinically significant reduction in symptom severity. In contrast, after completing a second course of CBT, 23% had HD symptom severity dropped below the cut‐off threshold, and 29% achieved clinically significant symptom reduction. Conclusions: The current study showed satisfactory feasibility and acceptability of CFT. Moreover, it also found promising effects of CFT in addressing hoarding‐related mechanisms that may not have been sufficiently addressed by CBT. The results suggest promising potential of CFT as a treatment for HD. Further investigation on this intervention is needed. Practitioner points: CFT may be a promising treatment option, particularly for those who do not respond well to CBT. Improving emotion regulation and negative self‐perception by applying CFT interventions may help relieve hoarding symptoms. Generalization of the findings should be applied with caution given the small convenience sample of the current study. Statistical comparison on treatment effect measures between CFT and CBT as follow‐up treatments was not available due to small sample size. Therefore, the comparative conclusions based on this pilot study should be made with caution.